1993
DOI: 10.1213/00000539-199310000-00021
|View full text |Cite
|
Sign up to set email alerts
|

The Orbicularis Oculi and the Adductor Pollicis Muscles as Monitors of Atracuriurn Block of Laryngeal Muscles

Abstract: The aim of this study was to determine whether atracurium-induced neuromuscular block at the laryngeal adductor muscles could be predicted by visual inspection of either adductor pollicis or orbicularis oculi responses. Twenty-one ASA Class I or II patients were anesthetized with propofol (2-2.5 mg/kg) and fentanyl (2-5 micrograms/kg). Tracheal intubation was performed without neuromuscular blocking drugs. Patients were assigned randomly to receive atracurium 0.3 or 0.5 mg/kg intravenously. Train-of-four stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 0 publications
0
13
0
3
Order By: Relevance
“…Time to disappearance of response to facial nerve stimulation was shorter in all groups, when compared with the adductor pollicis. A more rapid onset at the orbicularis oculi was observed before with vecuronium, 24 atracurium, 12,25 and mivacurium. 26,27 The response of the orbicularis oculi was recommended as a guide to intubating conditions because disappearance of response, as evaluated visually, was found to correlate with maximum blockade of laryngeal muscles.…”
Section: Discussionmentioning
confidence: 71%
“…Time to disappearance of response to facial nerve stimulation was shorter in all groups, when compared with the adductor pollicis. A more rapid onset at the orbicularis oculi was observed before with vecuronium, 24 atracurium, 12,25 and mivacurium. 26,27 The response of the orbicularis oculi was recommended as a guide to intubating conditions because disappearance of response, as evaluated visually, was found to correlate with maximum blockade of laryngeal muscles.…”
Section: Discussionmentioning
confidence: 71%
“…71 Several studies have described the relationship between the response at the eyebrow and either diaphragmatic response or intubating conditions. 42,[72][73][74][75] The movement of the eyebrow was evaluated either visually or by electromyography. Donati et al 42 found a striking resemblance in the time course of neuromuscular block between the eyebrow and the diaphragm.…”
Section: Anatomy and Physiologymentioning
confidence: 99%
“…Atracurium was chosen because its onset of action at the laryngeal and orbicularis oculi muscles had already been documented. 24 This value was considered to be similar between both muscle groups when it was reviewed recently. 25 Mean onset time after atracurium 0.5 mg·kg -1 observed in our study (166 ± 62 sec) was similar to that obtained in previous studies: 146 ± 55 sec, 24 141 ± 7 sec 26 and 129 ± 33 sec 27 after the same dose of atracurium.…”
Section: Discussionmentioning
confidence: 99%